2022
DOI: 10.3389/fonc.2022.860788
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Outcomes of Particulate Versus Coil Preoperative Embolization for Carotid Body Tumors

Abstract: Till now, the effect of different embolic materials (particulate vs coil) on pre-embolization of carotid body tumors remains poorly understood. The aim of this study was to explore the comparative results between particulate and coil embolization for carotid body tumors. Thirty-seven patients with carotid body tumors who underwent embolization before surgical resection were reviewed and analyzed in this retrospective study between 2008 and 2020. Twenty-one patients were included in the particulate group, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In most cases, the CBT receives its blood supply from the external carotid artery. Hence, several studies suggested that preoperative embolization might be an alternative method for preventing blood loss before surgery treatment (4,(7)(8)(9)(10). However, the preoperative embolization lengthens the overall treatment time of CBT, increasing the economic burden on patients as well.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the CBT receives its blood supply from the external carotid artery. Hence, several studies suggested that preoperative embolization might be an alternative method for preventing blood loss before surgery treatment (4,(7)(8)(9)(10). However, the preoperative embolization lengthens the overall treatment time of CBT, increasing the economic burden on patients as well.…”
Section: Introductionmentioning
confidence: 99%